Exocytotic exposure and retrieval of membrane antigens of chromaffin granules: quantitative evaluation of immunofluorescence on the surface of chromaffin cells (The Rockefeller University Press, 1984)
The exocytotic exposure of antigens of chromaffin granule membranes was studied with chromaffin cells isolated from bovine adrenal medulla. Antigens on the cell surface were visualized by indirect membrane immunofluorescence employing antisera against glycoprotein III and dopamine beta-hydroxylase. With unstimulated cells, only weak immunofluorescence on the cell surface was observed, whereas stimulated cells (with carbachol or Ba2+) exhibited much stronger reactions. In all cases the staining appeared as dots and patches. To quantitatively prove these observations, we analyzed the immunostained cells using a fluorescence-activated cell sorter. After stimulation, the average fluorescence intensity of the cell population was enhanced. This increase correlated with the degree of catecholamine secretion. The fluorescence intensity of stimulated cells varied over a broad range indicating that individual cells reacted variably to the secretagogues. When stimulated cells were incubated at 37 degrees C for up to 45 min after stimulation, a decrease of membrane immunofluorescence approaching that of unstimulated control cells was observed. Apparently, the membranes of chromaffin granules, which had been incorporated into the plasma membrane, were retrieved by a specific and relatively fast process. This retrieval of the antigen from the cell surface was blocked by sodium azide, but not influenced by colchicine, cytochalasin B, and trifluoperazine. The quantitative methods established in this paper should prove useful for further study of the kinetics of the exo-endocytotic cycle in secretory tissues.